SINERGI BUDAYA DAN KEBIJAKAN PUBLIK DALAM PENGEMASAN PARIWISATA BERBASIS KEARIFAN LOKAL DI KOTA TOMOHON: TELAAH ATAS FAKTOR POLITIK, SOSIAL EKONOMI, DAN LINGKUNGAN - Bida, Obed; Sigiro, Benny; Hadirman, Hadirman (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This research aims to examine the synergy between local culture and public policy in the packaging of local wisdom-based tourism in Tomohon City, North Sulawesi. The study focuses on identifying supporting and inhibiting factors across three main dimensions: (a) political aspects, related to regulations, permits, and budget allocation; (b) socioeconomic aspects, concerning community empowerment, job creation, and micro-enterprise development in the tourism sector; and (c) environmental aspects, including nature conservation, tourist area security, and ecotourism development. Using a qualitative approach through case studies, this research reveals that culture-based tourism packaging requires integration between the government, tourism operators, and local communities. The findings indicate that although local wisdom has significant potential in shaping destination identity, policy implementation is often hampered by weak inter-agency coordination, budget constraints, and low ecotourism literacy at the community level. Therefore, synergy between community-centered public policies and the preservation of local culture is key to realizing sustainable, inclusive, and equitable tourism.